Code-Switching of Regal Identity in the Early Modern Deccan. - RAYALA, SRI SATHVIK (Journal of the American Oriental Society)
The historiography of the early modern Quṭb Shāhī dynasty of southern India often wrangles with the question of regal identity. Some scholars, drawing primarily from Tĕlugu sources, have argued that the Quṭb Shāhīs became Indic rulers and adopted the regal customs traditionally expected of Tĕlugu monarchs. Others, drawing from Persian sources, have firmly located the regal identity of the Quṭb Shāhīs in the Islamo-Persianate domain. In this article I contend with this historiographic divergence. By focusing on the ruler Ibrāhīm Quṭb Shāh, I suggest that the reason for these antithetical analyses has much to do with how the Quṭb Shāhīs themselves presented their kingship. In particular I demonstrate that in Tĕlugu materials addressed to the Indo-Tĕlugu sociocultural domain, Ibrāhīm nurtured the image of an Indic sovereign fully conforming to the normative expectations of a Tĕlugu Hindu ruler. Simultaneously, in Persian materials addressed to the Islamo-Persianate sociocultural domain, he fostered the image of a pious Shiʿi monarch conversant with Persianate customs. This code-switching of regal identities, I argue, is indicative of how the Quṭb Shāhīs navigated and negotiated with the diversity that characterized their kingdom, which was situated at the intersection of the indigenous Indo-Tĕlugu domain and the more transregional Islamo-Persianate domain.